UNDERSTANDING THE DRIVERS OF QRIS ADOPTION IN ISLAMIC BANKS: THE MODERATING ROLE OF KNOWLEDGE - Arifiandi, M. Arfan; Rahmawati, Zulfa Muasaroh Binti; Miranti, Titis; Kornitasari, Yenny (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
This study aims to analyze the influence of Perceived Usefulness, Perceived Ease of Use, and Habit on the Decision to Use QRIS on Micro, Small and Medium Enterprises (MSME) consumers in Malang City, and to evaluate the role of Knowledge as a moderating variable in this relationship. This study uses a quantitative approach with data collection techniques through questionnaires to 384 respondents who are users of QRIS of Islamic Banks. Data analysis was conducted using the Structural Equation Modeling-Partial Least Square (SEM-PLS) method. The results of the study showed that Perceived Usefulness, Perceived Ease of Use, and Habit had a significant effect on the Decision to Use QRIS. In addition, Knowledge was proven to significantly moderate the entire relationship between Perceived Usefulness, and Habit on the Decision to Use. Meanwhile, Knowledge did not moderate the influence of Perceived Ease of Use on the Decision to Use QRIS Islamic Banks. This study provides implications for Islamic banking and MSME actors to improve consumer understanding of the benefits and ease of use of QRIS, as well as to know the Habits in adopting Islamic-based financial technology.